Comparison of strength and length of thermoset and thermoplastic elastomeric chains - Cortés Campos , Jazmin (2025)
Objectives: To compare the strength and length of thermoset and thermoplastic elastomeric chains. Materials and Methods: An in vitro study was performed with a sample of 72 thermoplastic and 72 thermoset chains, divided into 6 times groups (initial, 1, 7, 14, 21 and 28 days). Thirty-six templates were manufactured with 20 mm separation. To hold the chains at a constant length; they were immersed in artificial saliva. Housed in an incubator at 37° C. Force was measured with a dynamometer and length with a digital vernier caliper. Student’s t test, ANOVA and Tukey’s post hoc test were performed. Results: The mean initial force of the thermoset chains (309.58 g) was lower than of the thermoplastic chains, and at 28 days the thermoplastic chains (322.5 g) had a greater loss of force (46.2%) and the thermoset chains 35%. The thermoplastic chains had greater dimensional changes (49.9%) and the thermoset chains 28.6% of their initial length. The strength and length showed statistically significant differences (p<0.001) from the first day. Conclusions: The thermoplastic chains had greater initial strength, while the thermoset chains obtained a lighter but more durable strength. The thermoplastic chains showed greater length changes from the first day.